The Impact of Strabismus Surgery on Irish Adults. (24th April 2018) - Power, Barry; Murphy, Melissa; Stokes, John
Aims: Our primary objective was to evaluate our adult strabismus service and the impact strabismus surgery has on quality of life (QOL) in patients from an Irish cohort. Our secondary objective was to compare QOL outcomes across different subgroups. Methods: A service evaluation was prospectively performed over an 18-month period. We prospectively audited the preoperative and postoperative QOL scores from 35 adult strabismus procedures using the adult strabismus score (AS-20) (0–100). Results: Postoperative patients achieved an average 14.22 score increase in QOL (p = 0.0018). Females showed lower preoperative scores (46.78 vs. 60.89; p = 0.047) and a trend towards larger increases compared to males (21.05 vs. 51.12; p = 0.1). No significant difference was detected between primary and recurrent strabismus repairs (18.10 vs. 16.55; p = 0.4). Lower preoperative scores (0–33) were associated with higher increases compared with moderate (34–66) and high (67–100) preoperative scores (33.47, 12.03, –4.57 respectively). Patients reporting QOL score decreases after surgery were more likely to come from the high preoperative score group than the moderate or low groups (50%, 19% and 22% respectively). Conclusion: We demonstrate that strabismus surgery has a significant positive impact on QOL scores in Irish adults. We show that patients with high preoperative QOL scores may have a greater chance of QOL score decreases postoperatively, despite good clinical alignment. We believe greater preoperative discussion around patient expectations in these cases, may improve subjective postoperative results.